Binky the space cat - Spires, Ashley, 1978- (Toronto, ON ; Tonawanda, NY : Kids Can Press, 2009)
Binky, a house cat who believes the family home is actually a space station, trains and prepares to travel into outer space, where his humans go everyday and need his protection.
"A Binky adventure"--Cover.
Bulletin of the Center for Children's Books starre
Kirkus Starred
School Library Journal starred
3.0
3-6.
Keywords: Cats -- Comic books, strips, etc; Families -- Comic books, strips, etc; Cartoons and comics; Cats -- Fiction; Family life -- Fiction; Cats -- Comic books, strips, etc; Comic books, strips, etc; Family life -- Comic books, strips, etc; Graphic novels; Graphic novels